Batas Tindakan Homoseksual terhadap Hukum Pidana dan Hak Asasi Manusia di Indonesia - Agustina, Elvira; Taun, Taun (Peneliti.net, 2023)
In society, there are pros and cons to homosexuality, someone recognize that homosexuality is a way of life and everyone has the right to choose based on human rights, but some consider homosexuality is a sexual deviance. This paper studies whether homosexuality are criminal activities and whether there are limits to homosexual behavior that are considered criminal violations in Indonesia. This article employs normative research approaches and a literature-based methodology. As a result, homosexuality is legally regulated under Article 292 of the Indonesian Criminal Code. However, because the regulation does not regulate homosexual behavior between legal adults, etc. it cannot be prosecuted criminally. Therefore, it is critical that the policy of criminalizing homosexuality be implemented to safeguard society from the negative consequences of homosexual behavior.